Research on Formation Identification Based on Drilling Shock and Vibration Parameters and Energy Principle - Yu Ding; Zhuoying Tan; Shuguang Li; Zizhen Miao; Huifen Qu (Shock and Vibration)
In geotechnical engineering and geological survey, the stratum structure and its corresponding physical and mechanical properties are the most concerned. The stratum structure not only affects the safety of the project but also plays a decisive role in the construction method and construction sequence. In this paper, a new type of stratum geological interface recognition system is adopted, and an R-20 rotary drilling rig is used to conduct on-site drilling experiments for a granite site with no ventilation. The research results show that the system can monitor and record the main parameters (axial pressure, drilling rate, rotation speed, flushing fluid pressure, and torque) of the drilling rig during the drilling process. The comparative analysis of monitoring data and on-site survey results shows that different drilling parameters have different sensitivities to changes in the formation structure. According to the prediction accuracy, the ranking from high to low is drilling rate, axial pressure, torque, rotation speed, and flushing fluid pressure. In drilling engineering, by observing the change law of drilling rig parameters, not only can the position of the special rock mass interlayer be predicted, but also the stratum structure and strength can be identified, and the prediction formula is also given. Based on the established drilling specific energy formula, the energy analysis method is used to predict the formation structure and compressive strength, and the corresponding prediction formula is given. The research results show that, compared with the single drilling parameter prediction method, the rock-soil structure and strength identification method based on energy theory has higher prediction accuracy and can meet engineering needs.